2022
DOI: 10.3390/molecules27144457
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Fungi with Antiviral Effect

Abstract: Pandemics from various viruses make natural organisms face challenges over and over again. Therefore, new antiviral drugs urgently need to be found to solve this problem. However, drug research and development is a very difficult task, and finding new antiviral compounds is desirable. A range of medicinal fungi such as Ganoderma lucidum and Cordyceps sinensis are widely used all over the world, and they can enhance human immunity and direct anti-virus activities and other aspects to play an antiviral role. Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 143 publications
0
12
0
Order By: Relevance
“…The results showed that among the twenty-two edible mushroom proteins, the precious edible mushroom proteins were more common edible mushrooms and had higher immune activity. It was shown that medicinal fungi have a stronger immunomodulatory ability, and since CMP, CVP, IOP, TAP, MEP, and OSP are all valuable edible fungi, the reason for the stronger immunomodulatory effect of precious edible fungal proteins may be that medicinal fungi have some special proteins that are not found in common edible fungi ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that among the twenty-two edible mushroom proteins, the precious edible mushroom proteins were more common edible mushrooms and had higher immune activity. It was shown that medicinal fungi have a stronger immunomodulatory ability, and since CMP, CVP, IOP, TAP, MEP, and OSP are all valuable edible fungi, the reason for the stronger immunomodulatory effect of precious edible fungal proteins may be that medicinal fungi have some special proteins that are not found in common edible fungi ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…A serial of 80 natural compounds isolated from Ganodermaceae [ [10] , [11] , [12] , [13] , [14] , [15] , [16] ] was assembled for the molecular docking process, sourced from the database available at http://phytochem.nal.usda.gov ( Supporting information Table S1 ). The 3D structures of these compounds were retrieved from PubChem ( http://pubchem.ncbi.nlm.nih.gov ) and prepared using MarvinSketch (ChemAxon, Cambridge, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Although a mineral deficiency is rare, some mushrooms are a rich source of specific minerals (e.g., selenium, magnesium, and zinc), which may play a direct or indirect role in their anti-influenza properties, performing a crucial role in boosting the immune system and preventing the viral infections, and preserving the homeostasis process in the human body ( 128 ). Dried mushrooms might be a source of mineral components indispensable for human health ( 129 ).…”
Section: Antiviral Properties Of Mushroomsmentioning
confidence: 99%